Approaches to Public Personnel Management in the Digital Era and the Polycrisis Context - Tipmanee, Satit (Journal of Thai Ombudsman, 2026)
This research article aims to examine the problems, impacts, and propose approaches for public personnel management in the digital era and the context of polycrisis, encompassing challenges arising from technological transformation, economic change, and modern working arrangements. The study builds upon lessons learned from the COVID-19 pandemic and extends them to the design of public human resource management systems in the twenty-first century. This research adopts a qualitative documentary approach. It analyzes academic literature, research studies, reports of international organizations, and relevant legal and policy frameworks in Thailand and selected foreign countries in order to develop comparative policy recommendations. The findings reveal that major problems in public personnel management include the inability of organizational structures and work processes to keep pace with technological change, the decline of workplace relationships and social capital under hybrid working conditions, compartmentalized thinking in personnel policy formulation, deteriorating quality of working life and mental health, and the insufficient use of Big Data and foresight in policy decision-making. These challenges lead to reduced administrative efficiency and outcomes that fail to meet societal expectations. This study proposes the “BIIRR Model” as an innovative and integrated framework for public personnel management in the digital and polycrisis context. The model consists of Big Data, Importance, Integration, Relationships, and Remedies, integrating data-driven decision-making, strategic human resource management, whole-of-government coordination, workplace social capital, and personnel resilience into a unified framework. The BIIRR Model aligns with public sector reform principles advocated by the OECD and other international organizations, emphasizing flexibility, digital competencies, and hybrid work arrangements. It provides a practical policy framework for enhancing adaptability, sustainability, and effectiveness of public personnel management systems in Thailand.